Intercultural competency: A transformative learning process - Edward W. Taylor (Adult Education Research Conference, 1993)
This paper presents findings of a qualitative study which examined how adults learned to live and work successfully in cultures other than their primary culture. Discussed are theory, experiences, and skills essential to understanding the learning process of intercultural competency. The findings are explored within the context of transformative learning theory.